PERBANDINGAN KEMAJUAN KARIR ANTARA MANAJER WANITA DAN MANAJER PRIA DI INDONESIA - Setyaningtyas, Ruth Niken; Handoko, T. Hani; Harsiwi, Th. Agung M. (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2003)
This research that concerns managers' career progression in Indonesia was carried out in sixteen companies. It is intended to analyze the differences between female and male managers' career progression, by using human capital theory, family power theory, self-selection, industry differences, and also to examine the possibilities about discrimination. The research samples are managers who have been working at least for five years and have been geographically transferred (among cities) to promote their career. The method of sample determination was performed by purposive sampling. The data were obtained by interviews and distributing questionnaires directly and by mail. The respondents consisted of 40 female managers and 114 male managers, with a response rate of 34%. Statistical data processing was conducted by using hierarchial and full regression. The result of the analysis about managers' career progression in Indonesia show that female managers are lagged behind male managers in geographic mobility, but female managers are more advanced than male managers in salary progression and promotion. Discrimination doesn't take role in managers' career progression in Indonesia. Female managers who want to advance in career, have to be better in education than male managers’ education level.Keywords: career progression, human capital theory, family power theory, self-selection, industry differences